A catabogne on tite benthic marine flora of ida Tina Menor and Pechon’s coast (Cantabria, Spain) - Fernández-montero, Lidia; Gallardo, Tomás; Pérez-ruzafa, Isabel M.; Cubero, Ignacio (Botanica Complutensis, 1998)
FERNÁNDEZ-MONTERO, L.; PÉREZ-RUZAFA, 1. M. CUBERO, 1. & GAlLARDO, 1., 1997. A catalogue on the benthic marine flora of Ría Tina Menor and Pechón’s eoast (Cantabria, Spain). Rbi. Complutensis 22: 83-100. Samples, done in Ría Tina Menor and Pechón’s coast (Cantabria, Spain) during the aututu aud winterot 1995 andthe spring, summer and autum of 1996, sho’w a 11sf of 202 species (4 Cyanophyceae, 127 Rhodophyceae, 39 Phaeophyceae, 1 Chlorophyceae, ¡8 UIvophyceae, 6 Cladophorophyceae, 6 Brvopsidophyceac, and 1 Magnolioplmvta). Ihe number ol new records for Cantabria is 87.